Comparing nurse practitioners/physician assistants and physicians in diagnosing adult abdominal pain in the emergency department. Issue 11 (November 2018) - Hoyt, Karen Sue; Ramirez, Elda; Topp, Robert; Nichols, Stephen; Agan, Donna
ABSTRACT: Background and purpose: This retrospective study compared nurse practitioners and physician assistants (NPs/PAs) with physicians on their assignment of Emergency Severity Index level 3 (ESI level 3) acute abdominal pain (AAP) in the emergency department (ED). Methods: Data obtained from a large ED group staffing four hospitals yielded 12, 440 de-identified, adult patients diagnosed on ED admission with AAP ESI level 3 for descriptive analysis with logistic regression. Conclusions: Results revealed that the comparison of ESI level 3 AAP diagnoses was consistent between admission and discharge 95.3% for physicians, 92.9% for NPs/PAs, and 97.1% for NP/PA and physician collaboration (χ 2 = 46.01, p < .001). Logistic regression suggested that NP/PA had significantly reduced odds (31%) of consistent admitting/discharge diagnoses, whereas collaboration of NP/PA with physicians had significantly increased odds of consistent diagnosis (41%) compared with physicians alone. Two hospitals with similar distributions of NPs/PAs and physicians exhibited greater odds of consistent diagnoses over hospitals with disproportionate distributions; a secondary finding worth exploring. Consistent AAP ESI level 3 diagnoses by outcomes were admissions (>99%), discharges (94%), and left against medical advice/transferred (98%; χ 2 = 102.94, p < .001). Implications for practice: The highest percentage of consistent AAP ESI level 3 diagnoses between ED admission and discharge was when NPs/PAs and physicians collaborated.